2018
DOI: 10.1038/s41419-018-0640-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical isolates of the modern Mycobacterium tuberculosis lineage 4 evade host defense in human macrophages through eluding IL-1β-induced autophagy

Abstract: Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), has infected over 1.7 billion people worldwide and causes 1.4 million deaths annually. Recently, genome sequence analysis has allowed the reconstruction of Mycobacterium tuberculosis complex (MTBC) evolution, with the identification of seven phylogeographic lineages: four referred to as evolutionarily “ancient”, and three “modern”. The MTBC strains belonging to “modern” lineages appear to show enhanced virulence that may have warranted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 72 publications
3
54
2
Order By: Relevance
“…These results underscore the usefulness of the quantitative analysis of AIPD to monitor authophagy in macrophages infected with Mtb. Of note, we also observed autophagic flux induction in non-infected macrophages (in BCG-and Mtb-infected cells), probably resulting from the cytokines released by infected cells (24,25) that can act in paracrine mode.…”
Section: Cystamine Restricts Mtb Replication In Macrophages While Inhmentioning
confidence: 52%
See 4 more Smart Citations
“…These results underscore the usefulness of the quantitative analysis of AIPD to monitor authophagy in macrophages infected with Mtb. Of note, we also observed autophagic flux induction in non-infected macrophages (in BCG-and Mtb-infected cells), probably resulting from the cytokines released by infected cells (24,25) that can act in paracrine mode.…”
Section: Cystamine Restricts Mtb Replication In Macrophages While Inhmentioning
confidence: 52%
“…However, the role of basal autophagy in infected macrophages appears to be more complex. We have recently demonstrated that Mtb strains from ancient and modern lineages have a different impact on the basal autophagy flux (25). While the ancient lineages impair the autophagic flux, infection with the modern strains leads to a stimulation of this process, which is dependent on the increased production of IL1-β triggered by these mycobacteria (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations